Image segmentation for depth region identification - Raghavan, Arvind (2013)
Several recent applications require landscape photographs to be divided into depth- regions (foreground, middleground, background, sky). Currently, this segmentation is done manually, since depth-perception is itself a very subjective area, and none of the recent advances in image segmentation cater specifically to the unique features of depth-planes in landscapes. A method to automate or semi-automate this segmentation would make these applications considerably less cumbersome, especially in areas where large volumes of images are to be analysed.